ASSOCIATION BETWEEN BODY HEIGHT AND DOUBLE J STENT INTRAVESICAL POSITION AND ITS RELATION WITH THE INDONESIAN VERSION OF URETERAL STENT SYMPTOM QUESTIONNAIRE (USSQ) - Pramod, Sawkar Vijay; Siregar, Safendra; El Haq, Faris (Indonesian Journal of Urology, 2024)
Objective: This study aims to determine the relationship between the patient’s body height with the intravesical double J stent position and whether its position is related to the ureteral stent symptom questionnaire (USSQ). Material & Methods: A cohort study with a study population of patients inserted with double J stent size 4.7 Fr and length 26 cm was carried out at the Department of Urology Hasan Sadikin Academic Medical Center from July 2021 to July 2022. We assess the patient’s demographic features and different body heights into two categories, below and above average. Then we evaluate its stent position using a plain abdominal X-ray and the USSQ score. Results: Ninety samples were included in this study; 30 of them had a midline intravesical double J stent position, 30 pieces of contralateral, and 30 samples of ipsilateral. Only body height correlated to the stent’s position (p<0.05). The results of comparative statistical tests or the association of postoperative complications between 7 days and 30 days in the position of the double J stent midline, contralateral and ipsilateral had significant results (p<0.05). Stent with ipsilateral position showed a lower USSQ score. Conclusion: Men and women above the average height have a lower risk for migration stent to the contralateral side and are also associated with lower USSQ scores. Keywords: Double J stent, USSQ score, double J stent position.